Financial Distress Prediction Analysis using the Altman Z-Score Method in Tobacco Subsector Companies - Septiana, Nadia Widya; Rogahang, Joula J; Mukuan, Danny D. S. (Productivity, 2024)
This research aims to predict the occurrence of company financial distress conditions using the Altman Z-Score method with the object of research, namely tobacco subsector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The approach used in the research is a descriptive quantitative approach with secondary data sources. The data analysis technique used is using the Altman Z-Score method. The results showed that there was 1 tobacco company that was predicted to experience financial distress problems. While the other 3 tobacco companies are predicted to have a healthy and stable financial condition during the 2019-2022 period.